Impact of Donor Hemodynamics on Recipient Survival in Heart Transplantation - FU, SHENG; INAMPUDI, CHAKRADHARI; RAMU, BHAVADHARINI; GREGOSKI, MATHEW J.; ATKINS, JESSICA; JACKSON, GREGORY R.; CELIA, AMANDA; GRIFFIN, JAN M.; SILVERMAN, DANIEL N.; JUDGE, DANIEL P.; VAN BAKEL, ADRIAN B.; WITER, LUCAS J.; et al. (Journal of cardiac failure, 2023)
Heart transplantation is the gold-standard therapy for end-stage heart failure, but rates of donor-heart use remain low due to various factors that are often not evidence based. The impact of donor hemodynamics obtained via right-heart catheterization on recipient survival remains unclear. The United Network for Organ Sharing registry was used to identify donors and recipients from September 1999–December 2019. Donor hemodynamics data were obtained and analyzed using univariate and multivariable logistical regression, with the primary endpoints being 1- and 5-year post-transplant survival. Of the 85,333 donors who consented to heart transplantation during the study period, 6573 (7.7%) underwent right-heart catheterization, of whom 5531 eventually underwent procurement and transplantation. Donors were more likely to undergo right-heart catheterization if they had high-risk criteria. Recipients who had donor hemodynamic assessment had 1- and 5-year survival rates similar to those without donor hemodynamic assessment (87% vs 86%, 1 year). Abnormal hemodynamics were common in donor hearts but did not impact recipient survival rates, even when risk-adjusted in multivariable analysis. Donors with abnormal hemodynamics may represent an opportunity to expand the pool of viable donor hearts.